Time Management and Knowledge Management through Professional Competence in Teacher Performance - Juniarni, Selvi; Kaco, Rahmat; Asa'ad, Syarifuddin (Journal of Indonesian Scholars for Social Research, 2023)
This study aims to determine and elaborate on the effect of time management and knowledge management through professional competence on teacher performance in Mamuju. This study uses a causality design with a quantitative approach. The population in this study were all teachers in Mamuju. The sampling technique uses random sampling; the final sample is 100 teachers. Data collection techniques through questionnaires and documentation, during data analysis with path analysis. The study results show that with a direct effect, teacher performance can be improved by time management, where the teacher can manage the role of time management by setting clear goals, prioritizing, assertiveness, avoiding delays, and minimizing time. In addition, knowledge management also affects teacher performance; knowledge management is demonstrated by the ability of school organizations to identify, reflect, share, and use knowledge evenly. Professional competence is an intervening variable that has a significant role in improving teacher performance. In an indirect effect, professional competence acts as a moderating variable, where time management and knowledge management can encourage professional competence and impact teacher performance.